Enhancing E-Learning in the Educational Space in Grade 10 Dramatic Arts: A Trilingual Teacher’s Perspective - Sincuba, Limkani (Cultural Arts Research and Development, 2025)
South Africa takes pride in its rainbow nationality, which is spoken in twelve languages. Technology integration in arts education becomes paramount as educational settings evolve, particularly in diverse linguistic environments. English, isiXhosa and isiZulu may be one of the trilingual used by grade 10 in learning dramatic arts if e-learning may be enhanced in art schools in South Africa. The study investigated enhancing e-learning in the educational space in grade 10 dramatic arts trilingual teachers’ perspective through a trilingual approach involving English, isiXhosa, and isiZulu. In South Africa’s diverse linguistic space, the research employs a mixed-methods case study design centred on a single school offering Dramatic Arts. A purposive sample of 20 Grade 10 students and four educators was utilised to understand their experiences and perceptions of e-learning. Data were collected through questionnaires and focus interview. Data was coded and analysed to identify key themes. Findings revealed that incorporating trilingual resources and culturally relevant content significantly enhances students’ comprehension and appreciation of dramatic arts. The study further highlights the importance of interactive tools and collaborative projects in fostering an engaging learning atmosphere. By emphasising language as a medium for artistic expression, the research may contribute to the broader discourse on effective e-learning strategies in the arts, advocating for tailored approaches that recognise linguistic diversity. Ultimately, the study offers actionable insights for educators aiming to enrich their e-learning environments, ensuring that all students could thrive in their exploration of dramatic arts while celebrating their cultural identities.